Türkiye’ye İthal Edilen Kerevit Türlerinin Çevre Üzerine Oluşturabileceği Olumsuz Etkiler - Harlıoğlu, Muzaffer Mustafa; Farhadı, Ardavan (Fırat University, 2017)
Yaklaşık 15 kadar tatlısu ıstakozu (kerevit) türü lüks gıda maddesi olarak tüketilmeleri nedeniyle ekonomik önem taşır. Bu yüzden gıda maddesi olarak önem taşıyan bazı türler uzun yıllardan beri kıta içlerinde ve kıtalar arasında ekonomik fayda sağlamak amacıyla su kaynaklarına transfer edilmektedir. Son yıllarda kerevitlerin gıda olarak tüketilmelerinin yanında farklı renkteki bazı türler akvaryum sektöründe kullanılmak amacıyla doğal ortamlarından yabancı ülkelere ithal edilmektedir. Diğer taraftan, bu türler genelde daha saldırgan (doğal türü yok eden, büyük miktarda omurgasız, makrofit ve balık yumurtası tüketen), kanibalistik, barınak kazarak zemin yapısını bozan ve kendisi hastalıklara karşı nispeten dirençli olduğu halde taşındıkları ortamlara hastalık taşıyan türlerdir. Bu nedenle, başlangıçta ekonomik gelir elde etmek fikriyle yapılan kerevit ithalleri maalesef sonuçta çok az bir ekonomik getiriye karşılık geri dönüşü belki de mümkün olmayacak çevresel sorunlar oluşturmaktadır. Günümüzde, özellikle birçok Avrupa ülkesi ithal edilen türlerin oluşturdukları çevresel sorunlarla karşı karşıya bulunmaktadır. Ülkemize de akvaryum sektöründe kullanmak amacıyla son yıllarda sekiz kerevit türünün ithal edildiği bilinmektedir. Bu derlemede, ülkemizde bulunulan yabancı kerevit türlerinin doğal ortamlara ulaşmaları halinde çevre üzerine ne tür etkiler oluşturabileceği, stoklamalarda yaygın olarak kullanılan yabancı türlerin global ölçekte günümüze kadar oluşturduğu çevresel sorunlardan örnekler verilerek açıklanmaya çalışılmıştır

Approximately 15 freshwater crayfish species are economically important due to their consumption as a luxury food. For this reason some crayfish species that are important foodstuffs have been transferred into water resources for years to provide economic benefits between the continents and within the continents. In recent years, in addition to the consumption of crayfish species as a food resource, some species of different colors have also been imported from foreign countries into their natural environment in order to be used in the aquarium industry. On the other hand, these species are in general more aggressive (eradication of natural species, consuming great amount of invertebrate, macrophyte and fish eggs), cannibalistic, disrupting soil structure by digging shelter and although they are relatively more resistant to diseases, they are carrier of diseases to their new habitats. Therefore, imports of crayfish, initially made on the basis of economic income, unfortunately constitute environmental problems that can not possibly be reversed in return for very little economic return. Nowadays, especially many countries in Europe have environmental problems caused by non native crayfish species imports. It is known that eight crayfish species have been imported to Turkey in recent years for use in the aquarium industry. In this review, it is aimed to explain the environmental problems of the crayfish species, which are commonly used in stocking and the foreign crayfish type stockings which are formed on the global scale up to day by day, by examining the effects of foreign crayfish species found in our country on the environment. In this review, it is attempted to explain the environmental problems that alien crayfish species in our country could have on the environment if they reached the natural environment, by giving examples of the environmental problems common to the global scale of the alien species commonly used in stocking.
THE ADVERSE EFFECTS OF FRESHWATER CRAYFISH SPECIES IMPORTED TO TURKEY ON THE ENVIRONMENT